Issues in the Interpretation of “Altmetrics” Digital Traces: A Review - Xu, Shenmeng (Frontiers in Research Metrics and Analytics, 2018)
Researchers leave traces of their behavior during many stages of their research process. Parts of this process were formerly invisible. With scholarship moving online, we can now access various types of altmetrics digital traces such as reading, organizing, sharing and discussing scientific papers, thus develop a more holistic story about researchers and their work. However, a lack of in-depth interpretation of altmetrics digital traces is observed. Therefore, this paper focuses on reviewing some of existing altmetrics research, with a particular emphasis on the issues that need to be taken into consideration in the interpretation of altmetrics digital traces. Taking a preliminary step towards a guideline for more in-depth analysis of digital traces of scholarly acts, this review aims to bring attention to these issues to avoid misuse of altmetrics indicators.